The Heritage of Modern Architecture in the Context of the Interior: A Value Analysis of Kavaklıdere Cinema - Tür, Ayşe Nur; Şumnu, Umut (Ankara araştirmalari dergisi = Journal of Ankara studies, 2023)
The research deals with the conservation of modern architectural heritage with a focus on the interior. The user coming into direct contact with the interior makes it prone to subsequent interventions, although this also makes the protection of the interior space problematic. The research aims to address this problem through the consideration of a cinema structure in Ankara, namely Kavaklıdere Cinema. This Nejat Tekelioğlu apartment cinema building was built in 1965 and constitutes the sample of the research. In the first part of the research, the subject of the protection of modern architectural heritage is conveyed using a value-centered conservation approach. Different institutions and individuals have included definitions of value. In the following part, the emergence of cinema and its spatialization process are explained. In the final part, the interior analysis was conveyed through plans and interior photographs of the Kavaklıdere Cinema, which was chosen as a sample. An oral history interview was held with Ayhan Nergiz, the owner of the cinema, as well as with Zafer Şener and İrfan Demirkol, who have been the managers of the cinema for many years. Voluntary consent forms were obtained during the interviews. The personal archives of the interviewees were used as visual materials. Finally, Kavaklıdere Cinema was evaluated, according to the framework of the value-centered conservation approach, in terms of the value of the documents, identity, architecture, function and economic, continuity, memory, and originality. As a result of the evaluations, the features that Kavaklıdere Cinema should have in order to be considered as a modern architectural heritage have been analyzed, and the necessity of protecting the building has been emphasized. In addition to providing research, documentation and valuation, this study also serves as a basis for the work that needs to be done to protect Kavaklıdere Cinema.